Undoing Suicidism A Trans, Queer, Crip Approach to Rethinking (Assisted) Suicide - Baril, Alexandre (Temple University Press, 2023)
In Undoing Suicidism, Alexandre Baril argues that suicidal people are oppressed by what he calls structural suicidism, a hidden oppression that, until now, has been unnamed and under-theorized. Each year, suicidism and its preventionist script and strategies reproduce violence and cause additional harm and death among suicidal people through forms of criminalization, incarceration, discrimination, stigmatization, and pathologization. This is particularly true for marginalized groups experiencing multiple oppressions, including queer, trans, disabled, or Mad people. Undoing Suicidism questions the belief that the best way to help suicidal people is through the logic of prevention. Alexandre Baril presents the thought-provoking argument that supporting assisted suicide for suicidal people could better prevent unnecessary deaths. Offering a new queercrip model of (assisted) suicide, he invites us to imagine what could happen if we started thinking about (assisted) suicide from an anti-suicidist and intersectional framework. Baril provides a radical reconceptualization of (assisted) suicide and invaluable reflections for academics, activists, practitioners, and policymakers.